Food factory design: reality and challenges faced by Malaysian SMEs - Noor Hasnan, Noor Zafira; Ab. Aziz, Norashikin; Zulkifli, Norzima; Taip, Farah Saleena (Elsevier, 2014)
A competent food factory cannot be achieved if the factory is poorly designed. This paper identified the difficulties experienced by Malaysian small and medium enterprises (SME) in designing a food factory due to challenges faced by them. Two important manufacturing issues were analyzed and discovered to be related with poor factory design i.e. unsatisfactory food hygiene and lacking in sustainability. The analysis was based on a review of Malaysian data and literature. It is concluded that early considerations on food hygiene and sustainability can help SMEs to comply with hygiene standards, reduce cost and increase profit margin.